1998
DOI: 10.2307/2694113
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal and Social Implications of Ohio Hopewell Copper Ear Spool Design

Abstract: In a recent synthesis of style theory, Carr (1995) proposed a model based on attribute hierarchies, which reveal social patterns. The present study applies Carr's model of style to a large sample of bicymbal copper ear spools, a diagnostic “Hopewell” artifact class of the Middle Woodland period (ca. 150 B.C.—A.D. 400) in eastern North America. After ear spool attributes are defined and ranked for their visibility, a seriation of the ear spools is developed and tested for time and space correlations. Results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…The curation and deposition of a large quantity of obsidian debitage, as well as copper nuggets and partly worked copper, at the Hopewell site also suggest that production took place in the earthworks. K. Spielmann (2009) has suggested that earspool production, or at least their final assembly, may have been organized in workshops at earthwork sites given variation in disk construction within a single earspool and across earspools in the same pair (Greber and Ruhl 1989;Ruhl and Seeman 1998). Similarly, based on the fact that different kinds of yarns were included in individual textiles, multiple artisans may have worked on the same textile (Wimberly 2004).…”
Section: Worldmentioning
confidence: 96%
See 2 more Smart Citations
“…The curation and deposition of a large quantity of obsidian debitage, as well as copper nuggets and partly worked copper, at the Hopewell site also suggest that production took place in the earthworks. K. Spielmann (2009) has suggested that earspool production, or at least their final assembly, may have been organized in workshops at earthwork sites given variation in disk construction within a single earspool and across earspools in the same pair (Greber and Ruhl 1989;Ruhl and Seeman 1998). Similarly, based on the fact that different kinds of yarns were included in individual textiles, multiple artisans may have worked on the same textile (Wimberly 2004).…”
Section: Worldmentioning
confidence: 96%
“…The enduring tradition of skilled flaking of bifaces continued but their maximum size increased and risks were taken, such as completing large obsidian bifaces only after the raw material was brought to southern Ohio from Wyoming. Technological skill was required to craft the abundant copper earspools (Ruhl and Seeman 1998) and copper celts (Bernardini and Carr 2005). In contrast, most mica cut-outs would have been relatively simple to produce, requiring only a template, the raw material, and a sharp blade.…”
Section: Worldmentioning
confidence: 97%
See 1 more Smart Citation
“…Much of the production of Ohio Hopewell ritual items was concentrated within these earthworks. Crafting of certain ornaments, such as mica and copper cutouts, appears to have been carried out in these precincts by multiple craftspeople (Baby and Langlois 1979;Mills 1917;Ruhl and Seeman 1997). Likewise, the production of axes and other social valuables appears to have taken place in some British Neolithic causewayed enclosures, which, like Hopewell earthworks, were at least in part focused on mortuary ritual (Craddock et al 1983;Sharpies 1991).…”
Section: Organization Of Productionmentioning
confidence: 99%
“…Twenty more shafts indicated the scale and sustained practice (Strathern1969; Vial 1940). An archaeological example comes from the Ohio Hopewell, where a relatively mobile population that normally lived in small hamlets, congregated for communal rituals at geometric earthworks and produced thousands of copper ear spools (Ruhl and Seeman 1997). Additionally, Spielmann cites Damon and Wagner (1989) on the mortuary practices in the Papua New Guinea Massim for the time, effort, and resources used for community mortuary rites.…”
Section: Hypothesis: Ritual Production Modelmentioning
confidence: 99%